THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS' SCHOOL MANAGEMENT IN ANTICIPATING BUYING BEHAVIOR - Rohimah, Rohimah (Universitas Pakuan, 2024)
This research aims to examine and describe the unique processes and stages of school management at SMP Negeri 2 Tarumajaya Bekasi, which were developed to increase teachers' and students' understanding of the dangers of bullying. This type of research is qualitative, with a descriptive research approach. Data collection techniques were obtained through observation, documentation and interviews. The results of the School Management research show firstly, forms of bullying still exist at SMP Negeri 2 Tarumajaya, such as kicking and hitting, verbal non-physical in the form of cursing, mocking, calling names, accusing, giving encouragement, spreading gossip and shouting. , for mental or psychological bullying in the form of humiliating the victim and isolating the victim. The two factors that cause bullying at SMP Negeri 2 Tarumajaya are caused by parents' lack of attention to their children or those from families whose economic conditions are less fortunate. Third, the role of school management of Islamic Religious Education teachers in handling this case is to implement a friend teacher for students at SMP Negeri 2 Tarumajaya by positioning themselves as equals, taking an individual approach, as a partner to confide in and seeking empathy, attention, adopting a friendly attitude.